PRODUCTIVE ZAKAT USING THE QARDHUL HASAN SCHEME TO IMPROVE THE WELFARE OF THE ECONOMY - Mukaddis Mukaddis; M. Wahyuddin Abdullah (Universitas Islam Negeri Alauddin Makassar, 2019)
Poverty is an unresolved social problem. One solution to improve the welfare of the poor is the distribution of zakat and empowerment of zakat. The problem of zakat faced today is very complex, start from the fact that there are still some people who won't pay zakat until the distribution of zakat that has not been arranged neatly. The approach used in this research was desciptive qualitative.Descriptive qualitative research seeks to analyze and interpret data has been collected from the relevant literature. In distributing zakat there are two types of forms, namely consumptive and productive. Especially for zakat productive , giving this type of zakat to empower mustahik to be more productive, independent, and to improve their lives through their potential. Consumptive is understood that zakat is simple distributed such as zakat distributed in the form of zakat items which are used up or used up. Zakat is no longer scarred because it has been used in daily mustahik. However, productive zakat is distributed not to be spent but to be developed .The model of giving zakat productive includes business capital or loans to mustahik whose daily activities are economic activists, whether traders or others. One of the most suitable schemes to be applied in distributing productive zakat is qardhul hasan. This scheme was known as a loan that was given to someone for free without any imposition of fees unless only returning the principal. Distribution of zakat productive use the qardul hasan scheme make it easy and not burdensome for mustahik, and the qardhul hasan scheme will avoid usury, and mustahik can maximize it business income. The running distribution of zakat productive with the qardhul hasan scheme can be improve the people's economic welfare.